PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBANGUN KARAKTER DISIPLIN DAN BERTANGGUNG JAWAB PESERTA DIDIK PASCA PANDEMI COVID-19 DI SMAN 2 MALANG - Anbiya Kurnianingtyas; Rosichin Mansur; Imam Syafi'i (VICRATINA, 2022)
Character is an action that reflects the nature and character of a person. Character is divided into several parts, including disciplined and responsible characters which are closely related to students. During the Covid-19 pandemic, the character of students' discipline and responsibility has declined, at SMAN 2 Malang, including schools affected by the pandemic.Rebuilding the disciplined and responsible character of students is not an easy thing, because many students are still stuck in the comfort zone of studying at home. Thus, Islamic Religious Education teachers create special programs intended for students to rearrange the character of discipline and responsibility.